2012
DOI: 10.2147/ijn.s38127
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and osteogenic potential of a novel poly(lactic acid)/nano-sized β-tricalcium phosphate scaffold

Abstract: Abstract:The purpose of this study was to investigate the influence of nano-sized β-tricalcium phosphate (β-TCP) on the biological performance of poly (lactic acid) (PLA) composite scaffolds by using in vitro degradation and an in vivo model of heterotopic bone formation. Nano-sized β-TCP (nβ-TCP) was prepared with a wet grinding method from micro-sized β-TCP (mβ-TCP), and composite scaffolds containing 0, 10, 30, or 50 wt% nβ-TCP or 30 wt% mβ-TCP were generated using a freeze-drying method. Degradation was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Increased osteoconductivity and improved mechanical properties are documented for n beta TCP-coated poly(lactic acid) (PLL) scaffold, which depends on the n beta TCP ratio. 20 Several groups have observed that the incorporation of nano-HA into the gelatin increases the mineralization of the matrix and the alkaline phosphatase activity; this results in active bone growth in rat calvaria. 21,22 Also, the antimicrobial agents mixed with the nanoparticulate components for bone regeneration are thought to be more useful than traditional treatment, especially in cases of long-standing osteomyelitis.…”
Section: Nanostructured Scaffoldsmentioning
confidence: 99%
“…Increased osteoconductivity and improved mechanical properties are documented for n beta TCP-coated poly(lactic acid) (PLL) scaffold, which depends on the n beta TCP ratio. 20 Several groups have observed that the incorporation of nano-HA into the gelatin increases the mineralization of the matrix and the alkaline phosphatase activity; this results in active bone growth in rat calvaria. 21,22 Also, the antimicrobial agents mixed with the nanoparticulate components for bone regeneration are thought to be more useful than traditional treatment, especially in cases of long-standing osteomyelitis.…”
Section: Nanostructured Scaffoldsmentioning
confidence: 99%
“…Both dense and porous composites based on β-TCP have been demonstrated to show excellent performance in the physiological environment and possess several advantages over other calcium phosphates especially with regard to bioresorption [31][32][33][34][35][36]. In contrast only a few papers have been published on the fabrication of electrospun biodegradable hybrid fiber meshes containing β-TCP as inorganic component.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the incorporation of β-TCP into PLA materials can both enhance osteoconductivity and buffer acid products to reduce the inflammation around the implants. 9 Additionally, nano-sized β-TCP exhibits improved mechanical properties and tunable degradability compared with micro-sized powders. Therefore, it is a potentially promising approach to design composite fusion devices that combine the advantages of the two biodegradable materials and overcome the disadvantages of PLA.…”
mentioning
confidence: 99%